Photoionization of Trans-Fe Ions: Se IV, Se V, and Se VI - McLaughlin, Brendan M.; Wilms, Jörn; Babb, James F. (Atoms, 2025)
In the present study, the photoionization cross-sections are calculated for the trans-Fe ions Se IV, Se V, and Se VI over a wide energy region for ground and meta-stable states within the Dirac Atomic R-matrix approach (darc). Our cross-section results, when benchmarked against the available high-resolution measurements taken at the Advanced Light Source (ALS) for Se IV (Ga-like) and Se VI (Cu-like) selenium ions, show good agreement over the entire photon energy investigated. The present high quality cross-section data are suitable for use in many applications in astrophysics.
CRIS-Team Scopus Importer:2025-05-02
Keywords: atomic data; atomic processes; cross-sections; photoionization; relativistic; scattering